2019
DOI: 10.1016/j.molcel.2019.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Classes of Chromatin Loops Revealed by Deletion of an RNA-Binding Region in CTCF

Abstract: R.T. conceived the project. C.C., A.S.H., and I.P. performed genome editing and generated cell lines. A.S.H. characterized the C59D2 line (growth rate, cell cycle, and protein abundance). C.C. and I.P. performed and analyzed biochemistry experiments including western blots and coIPs. C.C. performed in vitro RNA-binding assays. R.S.-M. performed PAR-CLIP. D.R. supervised PAR-CLIP. A.S.H. performed and analyzed imaging experiments. T.-H.S.H. performed and analyzed Micro-C experiments. C.C. performed and analyzed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
215
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(244 citation statements)
references
References 111 publications
28
215
0
1
Order By: Relevance
“…There is some controversy about which region of CTCF interacts with cohesin. While one report demonstrates physical interaction between the C terminal region of CTCF (amino acids 575 to 611) and the SA2 subunit of cohesin [37], other studies that deleted these amino acids (577-614) showed that they are dispensable [36, 55, 56]. In agreement with others, we find that RAD21 overlaps with CTCF binding and does not occupy sites bound exclusively by CTCFL ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…There is some controversy about which region of CTCF interacts with cohesin. While one report demonstrates physical interaction between the C terminal region of CTCF (amino acids 575 to 611) and the SA2 subunit of cohesin [37], other studies that deleted these amino acids (577-614) showed that they are dispensable [36, 55, 56]. In agreement with others, we find that RAD21 overlaps with CTCF binding and does not occupy sites bound exclusively by CTCFL ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, clustering analysis of binding at CTCF and CTCFL only sites revealed that CLC is able to bind weakly to some CTCF only sites when CTCF is present but not when it is absent ( Figure S5D ), indicating that perhaps the N and C terminals of CTCF facilitate interaction between CTCF and CLC and this in turn directs binding of CLC to these sites. In support of this idea, recent studies have shown that an RNA binding region on the C terminal region of CTCF mediates CTCF clustering [56, 58]. Examples of fusion and parent protein binding are shown in the screenshots in Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Micro-C replaces the restriction enzyme used in Hi-C with micrococcal nuclease for digestion. Several groups recently used Micro-C to generate high-resolution contact maps of mouse and human cells highlighting its advantages over Hi-C and its potential to become an essential assay for nucleome studies [11,12]. The objective here was to assess the performance of Mustache on Micro-C data and evaluate the consistency of Micro-C loops when compared to Hi-C loops on the same cell line.…”
Section: Mustache Detects Loops That Are Consistent Between Hi-c and mentioning
confidence: 99%
“…To date, Hi-C has been the main assay of choice for discovering genome-wide chromatin contacts/interactions [8,9]. More recently, Micro-C [10], which replaces the restriction enzyme in Hi-C with micrococcal nuclease for digestion, enabled the generation nucleosome resolution chromosome folding maps of mouse and human cells [11,12]. With the decreasing cost of sequencing and optimization for smaller cell numbers, both Hi-C and Micro-C assays are expected to produce much higher resolution reference contact maps for a diverse set of organisms and cell lines [9,13,12].…”
Section: Introductionmentioning
confidence: 99%